Medicinal Botanicals in the Traditional Medicine of the Veps Used for Bronchial Infections - Barnaulov, Oleg D.; Barnaulov, A.O. (Current Traditional Medicine, 2018)
This article gives a short survey of the medicinal botanicals applied in the traditional medicine of the Veps, a small Finno-Ugric people, to treat severe respiratory infections— bronchitis, pneumonia, and tuberculosis of the lungs. Attention is focused on the methods of preparing the medicines, both simple and more complex medicinal forms. Veps' traditional healing (znakharstva) applies medicinal botanicals with charms or spells. Nevertheless, we emphasize the scientific foundation and the efficacy of Veps popular medicine, that uses rare, rather than common plants.
Keywords: Veps